i
i^1 = i
i^2 = -1
i^3 = -i
i^4 = 1
So, i^49 is i^48 (which is i^4 multiplied by itself 12 times) times i.
So i^49 = i.
2007-07-05 10:27:40
·
answer #1
·
answered by Justin L 4
·
2⤊
0⤋
i^48 = 1
so i^49 = i
2007-07-05 17:28:26
·
answer #2
·
answered by spirit dummy 5
·
0⤊
0⤋
i is the square root of -1, so i^2 = -1 and thus i^4 = 1.
i^49 = i * i^48 = i
since i^48 = 1^12 = 1.
2007-07-05 17:28:18
·
answer #3
·
answered by MathProf 4
·
1⤊
0⤋
You know that:
i^1 = i
i^2 = -1
i^3 = -i
i^4 = 1
and it continues in that pattern, so i^5=i, i^6=-1, etc
Now, i^49 can be written as (i^48)*(i^1)
Since 48 is a multiple of 4, i^48 = 1,
so (i^48)*(i^1) = 1*(i^1) = i
i^49 = i
2007-07-05 17:31:46
·
answer #4
·
answered by nona 3
·
1⤊
0⤋
i^49 = i^48*i = i
2007-07-05 17:27:58
·
answer #5
·
answered by ironduke8159 7
·
1⤊
0⤋
i^49 = i
2007-07-05 17:28:33
·
answer #6
·
answered by oregfiu 7
·
0⤊
0⤋
First, express 49 as 2(24) + 1
i^49 =
i^(2(24) + 1))
Use exponential properties to separate and solve.
i * i^(2(24))
i * (i^2)^24
But we know i^2 = -1, so we get
i * (-1)^24
And we know (-1) to an even power is +1, so we have
i * (1)
or simply
i
2007-07-05 17:28:08
·
answer #7
·
answered by Puggy 7
·
1⤊
1⤋
i = sqrt(-1)
i^2 = -1.
i^48 = -1^24
-1^24 = 1
i^49 = 1i
2007-07-05 17:28:42
·
answer #8
·
answered by TadaceAce 3
·
0⤊
0⤋
Its a constant, there is no solving to be done.
2007-07-05 17:27:56
·
answer #9
·
answered by sd d 3
·
0⤊
6⤋